Review artikel: metode analisis dalam pengujian kandungan pewarna merah K10 (Rhodamin B) pada kosmetik - Vista Kamilania; Patihul Husni (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Cosmetics are products used to improve the appearance of the outer body. Cosmetics are inseparable from dyes. One dye that is often misused in cosmetic products is Rhodamine B. Rhodamine B can cause liver damage and irritation of the respiratory tract and is carcinogenic. This review article aims to provide information on the use of analytical techniques to identify cosmetic products containing rhodamine B. The method used is a literature review by searching research journals with a period of 2013-2023 on Science Direct and Google Scholar using the keywords